Proposta de carta de serviço ao usuário para o Núcleo de Educação da Infância Colégio de Aplicação da UFRN (NEI/CAP-UFRN) - Santos, Ana Cleia Targino Dos (2020)
Currently, much has been discussed about access to information in public organizations and how they are managing the resources availableto provide a quality service. The way services are performed and offered is a matter of public interest, and therefore requires transparency and easy access to this information. The Brazilian Public Administration has been adopting ways of providing instruments for consultation and social control. Among these instruments, the User Service Charter stands out, currently regulated by Federal Decree no. 9.094 / 2017 that aims to inform citizens about the services offered by a Public Organization, as well as the ways to access them. Thus, the general objective of the research is to develop a proposal for a User Service Letter for the Núcleo de Educação da Infância, Application College of the Federal University of Rio Grande do Norte -UFRN (NEI/CAp-UFRN). Moreover, from that, check how the construction of this document can contribute to the insertion of better institutional practices in line with the greater primacy of the Managementmodel of Public Administration. As a research method, a qualitative approach with a descriptive objective was adopted, and concerning technical procedures, the study is characterized as documentary research and observation by the researcher